Extreme Psycho-Emotional Stress for Kharkivites Caused by Russia-Aggressor Bombardments: Ways to Overcome - Ivanchenko, Andreyanna; Khrystenko, Vitalii; Ovsyannikova, Yanina; Zaika, Evgenij; Perepeliuk, Tetiana; Osadchenko, Inna (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: This psychological research, conducted in the first months of the war, was carried out for the first time in world scientific practice. Our aim was to present the missing mathematical-statistical assessment of the emotional response and psycho-physiological state of civilians who, from the first day of the war, were in Kharkiv, constantly under Russian-aggressor fire. Methods: 585 Kharkiv participants were tested using the only possible means accepted during constant rocket attacks and hostilities (visual psychodiagnostics methods). Results: Negative mental manifestations and the disability of Kharkivites to manage their psycho-emotional state have been established. Their evolution has been traced. The time stages of the participants’ states were identified and characterized. Nearly all participants demonstrated intense stress-induced arousal and psycho-emotional incapacity/inability. Psychotrauma also developed among Kharkivites, who constantly monitored military events through social Internet networks. Children were the most susceptible to all severe sensations. Conclusions: The identified conditions are dangerous because they lead to pathological neurological-somatic disorders, psycho-emotional incapacity, or disability due to the stress-induced somatic-physiological destruction of the body. To normalize the psycho-emotional self-awareness and to help the participants get out of a stressful state, various preventive-rehabilitation means were used.